The Sentence Is Most Important: Styles of Engagement in William T. Vollmann’s Fictions (ENTHYMEMA, 2019)
William T. Vollmann frequently asserts that his ideal reader will appreciate the functionality and beauty of his sentences. This article begins by taking such claims seriously, and draws on both literary and rhetorical stylistics to explore some of the many ways that his texts answer to his intention to find “the right sentence for the right job.” In particular, this article argues that Vollmann’s stylistic decisions are most notable when they most directly satisfy his effort to produce texts that foster empathetic knowledge, serve truth, resist abusive power, and encourage charitable action. Extended close analyses of passages from an early and from a mid-career text (The Rainbow Storiesand Europe Central) illustrate Vollmann’s consistency across two decades of his career regarding choices in the areas of figuration (including schemes and tropes of comparison, repetition, balance, naming, and amplification), grammar, deixis, allusion, and other compositional strategies. Particular attention is paid to passages that display the stylistic mechanisms underlying Vollmann’s negotiation of his texts’ moral qualities, including both the moral content of the worlds represented in the texts, and the moral responsibility the texts bear with regard to their audience. The results of my analyses demonstrate that Vollmann typically prioritizes openness, critique, and dialogue not only in terms of incident and character, but also on the scale of the phrase, clause, and sentence. Ultimately, this article shows how Vollmann’s sentences serve his declared intentions and allow readers to recognize compatibilities between Vollmann’s works and the characteristic features of post-postmodernist writing in general.
Keywords: William T. Vollmann; Style; Contemporary American fiction